Embryotoxicity of nitrophenols to the early life stages of zebrafish (Danio rerio). (August 2016) - Ceylan, Zeynep; Şişman, Turgay; Yazıcı, Zehra; Altıkat, Aysun Özen
The nitrophenols (NPs) are water-soluble compounds. These compounds pose a significant health threat since they are priority environmental pollutants. In this study, 2-Nitrophenol (2NP) and 2, 4-dinitrophenol (DNP) were examined for embryo and early life stage toxicity in zebrafish ( Danio rerio ). Acute toxicity and teratogenicity of 2NP and DNP were tested for 4 days using zebrafish embryos. The typical lesions observed were no somite formation, incomplete eye and head development, tail curvature, weak pigmentation (≤48 hours postfertilization (hpf)), kyphosis, scoliosis, yolk sac deformity, and nonpigmentation (72 hpf). Also, embryo and larval mortality increased and hatching success decreased. The severity of abnormalities and mortalities were concentration- and compound-dependent. Of the compounds tested, 2, 4-DNP was found to be highly toxic to the fish embryos following exposure. The median lethal concentrations and median effective concentrations for 2NP are 18.7 mg/L and 7.9 mg/L, respectively; the corresponding values for DNP are 9.65 mg/L and 3.05 mg/L for 48 h. The chorda deformity was the most sensitive endpoint measured. It is suggested that the embryotoxicity may be mediated by an oxidative phosphorylation uncoupling mechanism. This article is the first to describe the teratogenicity and embryotoxicity of two NPs to the early life stages of zebrafish.